KONTRIBUSI KEKUATAN OTOT TUNGKAI DAN KOORDINASI MATA-KAKI TERHADAP KEMAMPUAN SEPAK SILA PERMAINAN SEPAK TAKRAW PADA MAHASISWA PUTRA STKIP PARIS BARANTAI KOTABARU - Arham Syahban (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2018)
This study aims to determine the Contribution to leg muscle strength and eye-foot coordination to the ability of sepak sila to play the sepak takraw game of male students of STKIP Paris Barantai Kotabaru. The research method used is descriptive quantitative method with data collection techniques using test and measurement techniques for leg muscle strength and eye-foot coordination and their respective contributions to the sepak sila skills of the sepak takraw game. The population of this study were all male students of the STKIP Paris Barantai Kotabaru. Samples were taken as many as 30 male students using the sampling method, namely simple random sampling. From the results of the study it was found that there was a contribution of leg muscle strength (X1) to the sepak sila ability of the sepak takraw game of male students STKIP Paris Barantai Kotabaru (Y). There is a contribution of eye-foot coordination (X2) to the ability of sepak sila to play the sepak takraw game of male students STKIP Paris Barantai Kotabaru (Y). There is a contribution of leg muscle strength (X1) and eye-foot coordination (X2) jointly to the sepak sila ability of the sepak takraw game of male students STKIP Paris Barantai Kotabaru (Y) Keywords: Leg Muscle Strength, Eye-foot Coordination, Sepak Sila Ability, Sepak Takraw.